Socio-economic development of border municipalities: the cases of Vyborg and Sortavala - Dmitry Zimin (European Regional Science Association (ERSA), 2003)
Since the early 1990s, when the permeability of the Russian-Finnish border has been considerably improved, border municipalities on the Russian side have been increasingly involved in a multitude of cross-border social and economic contacts. These contacts have included tourism, 'shuttle-trade', cultural exchanges, business co-operation, migration, and others. The objective of this paper is twofold. First, it attempts to measure the impact of cross-border contacts on the development of two Russian border municipalities: Vyborg and Sortavala situating in the Leningrad province and in the Republic of Karelia respectively. This analysis is carried out through a comparison of social and economic dynamics in the border and non-border municipalities situating in the same regions. Thus, Vyborg is compared with the Podporozhie municipality of the Leningrad province, while Sortavala is compared with the Pudozh municipality of Russian Karelia. Second, on the basis of the above observations the paper seeks to propose a theoretical framework for an analysis of the cross-border relationship and its likely future evolution. The paper concludes with the idea that at present we witness a 'knowledge-accumulation' stage of cross-border relations at which cross-border actors operating on the Finnish and Russian side acquire the knowledge of how to deal with each other. As a result, it is possible to envisage the emergence of some knowledgeable cross-border stakeholders, who might in the near future become a real manifestation of further cross-border integration along the Finnish-Russian border.
Keywords: 330